Acute pulmonary edema. The therapeutic approach. - Ceia, F (1995)
The management of acute pulmonary edema remains an interesting challenge to the clinician. The early recognition of this frequent condition, based on clinical features, must lead to the institution of general measures of therapy that can save most patients; a delay or mistake in this early treatment is lethal. The subsequent treatment depends on the characterization of the etiology and the pathophysiological characteristics of each case. The authors present a review of the management of acute pulmonary edema for the general practitioner, which includes the general first line measures and also mention some therapeutic approaches, related to different etiologies, namely those requiring intensive care units.